Binder-free Co–Ni hexacyanoferrate as a battery-type electrode material for hybrid supercapacitors. Issue 8 (15th April 2022) - Bommireddy, Purusottam Reddy; Chandra Sekhar, M.; Lee, Young-Woong; Kumar, Mirgender; Suh, Youngsuk; Park, Si-Hyun
Abstract: In this study, Co–Ni hexacyanoferrate (Cox Ni3-x HCF) electrodes with different Co and Ni ratios were directly synthesized on Ni foam (NF) via a simple and cost-effective hydrothermal approach, and their physical and electrochemical properties were studied. The binder-free Cox Ni3-x HCF@NF composites exhibited battery-like electrochemical storage mechanisms. Among them, the CoNi2 HCF@NF composite exhibited the better charge storage properties with a specific capacity of 817 C g −1 at 1 A g −1 . Furthermore, a hybrid supercapacitor (HSC) device with a CoNi2 HCF@NF composite as the battery type and activated carbon as supercapacitor electrodes delivered a high energy density of 36 Wh Kg −1 at a power density of 1056 W kg −1 along with good cycling performance. This study introduces a feasible method to design such binder-free materials with optimized synergetic effects that are beneficial for designing next-generation HSC devices.